Rural Crime Studies in Turkey: A Systematic Literature Review - Talha Şenol (Ceza Hukuku ve Kriminoloji Dergisi)
Crime research on rural areas in Turkey has not been adequately addressed in general crime research and has become a neglected are of research. However, the phenomenon of crime in rural areas and the necessity of generating solutions to this phenomenon is a reality. This study aims to systematically review the very limited rural crime studies and present a literature review. This study focuses on crime studies in rural areas in Turkey. All kinds of research such as articles, books, and theses written in Turkish and English on the subject were included in scanning the determined databases. It is assumed that the study will benefit rural crime researchers in terms of seeing the field more clearly, which studies are more focussed, which methods are used more, and what kind of gaps are in the field. According to the results of the study, it was observed that forest crimes were studied extensively, and there was a slow increase in the studies of public order crimes in rural areas. In addition, it is interpreted that quantitative researche relatively dominant in the field and that more qualitative research on the causes of crime is needed.